Current status and future prospects of soybean and oil crop production in Zhejiang Province - ZHANG Hui; HUAI Yan; ZHOU Weijun; FENG Yue; WANG Yuexing (浙江大学学报. 农业与生命科学版, 2023)
This paper summarized the current status of soybean and oil crop production in Zhejiang Province and China in recent years, and focused on analyzing the characteristics of soybean and oil crop production and the problems and challenges faced by the industrial development in Zhejiang Province. Combining the actual situation of “nongrain” cultivated land remediation in Zhejiang Province, this paper proposed to fully utilize the winter fallow fields, deeply exploit the planting potential, expand the sown area of soybean and oil crops, and increase their production capacity, so as to realize the sustainable development of soybean and oil crop industries in Zhejiang Province by extending the multiple uses of oil crops, promoting new planting modes, and improving mechanization levels.